A STUDY OF MAX WEBER THOUGHT ON ITS RELATION TO WORK PURPOSES AND ETHICS IN THE ISLAMIC ECONOMICS - Alfina Rahmatia (Transformatif, 2019)
This study seeks to expand the horizon of existing literatures on the Max Weber thought and its influence towards the Islamic economics view. This study uses library research method and web research method. It answers question about the theory of Max Weber and how its influence towards Islamic economics development, particularly in work purposes and ethics. This study compares Max Weber thought and Islamic view about economic in which the economic activity that is criticized by the work and ethic in Islam. In the end of this study shows that rationality theory from Max Weber is not in line with the Islamic economics view completely.